Cinema and television in Singapore : resistance in one dimension - Tan, Kenneth Paul (Social sciences in Asia, 2008)
"Through close readings of contemporary made-in-Singapore films (by Jack Neo, Eric Khoo, and Royston Tan) and television programs (Singapore Idol, sitcoms, and dramas), this book explores the possibilities and limitations of resistance within an advanced capitalist-industrial society whose authoritarian government skillfully negotiates the risks and opportunities of balancing its on-going nation-building project and its "global city" aspirations. This book adopts a framework inspired by Antonio Gramsci that identifies ideological struggles in art and popular culture, but maintains the importance of Herbert Marcuse's one-dimensional society analysis as theoretical limits to recognize the power of authoritarian capitalism to subsume works of art and popular culture even as they attempt consciously - even at times successfully - to negate and oppose dominant hegemonic formations."--Jacket